TO ASSESS RELATIONSHIPS BETWEEN LACTATE CLEARANCE AND BLOOD LACTATE LEVELS WITH OUTCOME OF NEONATAL SEPSIS - chaudhry, Shumaila; Haroon, Farah; Khawaja Ahmed Irfan Waheed; Victor , Gideon; Shahzad, Muhammad; Fatima , Bushra (Journal of Ayub Medical College Abbottabad, 2022)
Background: Sepsis is life-threatening organ dysfunction caused by dysregulated host response to infection. Aim of the study is Neonatal sepsis refers to infection involving the blood stream in neonates. It is major health problem causing neonatal mortality and morbidity in developing countries. Our study aimed to assess the correlation between lactate clearance and blood lactate levels with outcome of neonatal sepsis. Methods: Seventy-three eligible neonates recruited with convenience sampling technique. Study was conducted at the Neonatology department, The Children's Hospital & the Institute of Child Health, Lahore. After approval from institutional review board, and informed consent of parents/guardians, neonates with sepsis were selected through a present inclusion and exclusion criteria. Data was collected with the predetermined demographics, inflammatory markers and lactate levels. Results: This research revealed 37% (n=27) mortality rate among septic neonates who were having higher blood lactate levels and low lactate clearance at 6 hours of admission in nursery. Hence higher serum lactate levels and low lactate clearance (<10%) at 6 hours were significant predictors of poor outcome in septic neonates (p-Value, <0.05). The lactate level of neonates who could not survive was 5.68±1.22 as compared to who were discharged 4.11±1.14 (p-Value, <0.05). Conclusion: Higher blood lactate levels and lactate clearance of less than 10% at 6 hours of admission in nursery are significant predictors of mortality in neonatal sepsis. Early lactate stabilization and sepsis management can improve the clinical outcomes.